Marketing mix to increase enrollment in training of the Mexican Social Security Institute - Gutiérrez-Méndez, Julio; Karam Araujo, Roberto Karam Araujo; Fiol Manríquez, Luis Alonso (Horizonte Sanitario, 2019)
Objective: To evaluate the impact of the marketing mix in the increase enrollments training services at the Mexican Social Security Institute. Materials and methods: Analytical, observational, longitudinal and retrospective study of 6 years in the trend in enrollment training programs based on the use of marketing mix. The Pearson R test was applied to correlate the variables: price, place, positioning, product and promotion with the number of entries. Results: An increase in registrations of 167% was found after using the marketing mix in the Mexican Social Security Institute through face-to-face, distance and labor training. Conclusions: The marketing strategies applied from 2008 to 2013 were the diversification of the product (services “courses, workshops, talks”); the continuity or exemption in prices; the variation in the offer of new places to access the training; use of various means of promotion; as well as a positioning of the Social Benefits. Once established the relationship between the marketing mix and the level of increase in enrollments based on the Pearson R test resulted in a degree of significance of 0.839. Marketing can be applied to private, social and public institutions. Keywords: Marketing, Social security; Health system.